The Changes of Provident Thinking as a Regulative Idea in the Sciences - Nowak , Karolina (Studia Oeconomica Posnaniensia, 2017)
The paper touches upon the situation of previdism thinking in the social sciences (especially in sociology). The changes of provident thinking as a regulative idea in the sciences from naturalism to antinaturalism have been presented. The main goal of paper is to present a new modern functional form of previdism, predictions and prognosis in the social sciences, which is connected with the process of redefining the social roles of the social sciences in society, and the process of the marketization of the world of science including changes of visions within scientific establishments.